On the Connection Between Annual Variations of the Intensity of Galactic Cosmic Rays and the Changeability of Cloudiness and Air Temperature in Tbilisi - Amiranashvili, Avtandil G.; Bakradze, Teimuraz S.; Ghlonti, Nugzar Ya.; Khurodze, Tamila V.; Tuskia, Irakli I. (Journals of Georgian Geophysical Society, 2017)
The paper considers the results of the study of the connection between annual variations of intensity of galactic cosmic rays and the changeability of cloudiness and air temperature in 1963-1990 in Tbilisi. The statistical characteristics of the indicated parameters (trends, random component, linear correlations between real and random components, etc.) are studied. In particular, we established that the correlation of the real values of cosmic ray intensity with the real values of total cloudiness is positive, with lower cloudiness – is not significance, with air temperature – is negative. The correlation of the random components of the intensity of cosmic ray intensity with the random components of lower and total cloudiness – are positive, with the air temperature - is negative. Within the variation range the contribution of the studied parameters to air temperature variability is as follows: real values of total cloudiness- 5.0%, random components of lower cloudiness – 1.0%, real values and random components of cosmic ray intensity - 3.0% and 4.1%, respectively.